Thermal stability of tungsten-boron-nitride thin film as diffusion barrier - Park, YK; Kim, SI; Kim, YT; Lee, CW (KOREAN PHYSICAL SOC, 2000)
The electrical and the structural properties of tungsten boron nitride (W-B-N) thin films were studied to investigate the effects of boron and nitrogen in the 1000 Angstrom W-B-N diffusion barrier. The W-B-N thin films were deposited by using the RF magnetron sputtering method. The impurities provided a stuffing effect that was very effective for preventing interdiffusion between the interconnection metal and the silicon during the subsequent high-temperature annealing process. The resistivities of the W-B-N thin films were in the range of 140 - 406 mu Omega-cm, depending on the partial pressure ratio of the N-2 gas and the RF power density of the W2B5 target. XRD and electrical-property analyses showed that the W-B-N barriers did not react with Si during the annealing in N-2 gas ambient, even for annealing at 1000 degrees C for 30 min.